Anti-inflammatory effects of cordycepin in lipopolysaccharide-stimulated RAW 264.7 macrophages through Toll-like receptor 4-mediated suppression of mitogen-activated protein kinases and NF-κB signaling pathways - Choi YH; Kim GY; Lee HH (Dove Medical Press, 2014)
Yung Hyun Choi,1,2 Gi-Young Kim,3 Hye Hyeon Lee4 1Department of Biochemistry, Dongeui University College of Korean Medicine, Busan, 2Anti-Aging Research Center and Blue-Bio Industry RIC, Dongeui University, Busan, 3Laboratory of Immunobiology, Department of Marine Life Sciences, Jeju National University, Jeju, 4Daegu Gyeongbuk Institute of Science and Technology, Daegu, Republic of Korea Abstract: Cordycepin is the main functional component of the Cordyceps species, which has been widely used in traditional Oriental medicine. This compound possesses many pharmacological properties, such as an ability to enhance immune function, as well as antioxidant, antiaging, and anticancer effects. In the present study, we investigated the anti-inflammatory effects of cordycepin using a murine macrophage RAW 264.7 cell model. Our data demonstrated that cordycepin suppressed production of proinflammatory mediators such as nitric oxide (NO) and prostaglandin E2 by inhibiting inducible NO synthase and cyclooxygenase-2 gene expression. Cordycepin also inhibited the release of proinflammatory cytokines, including tumor necrosis factor-alpha and interleukin-1-beta, through downregulation of respective mRNA expression. In addition, pretreatment with cordycepin significantly inhibited lipopolysaccharide (LPS)-induced phosphorylation of mitogen-activating protein kinases and attenuated nuclear translocation of NF-κB by LPS, which was associated with abrogation of inhibitor kappa B-alpha degradation. Furthermore, cordycepin potently inhibited the binding of LPS to macrophages and LPS-induced Toll-like receptor 4 and myeloid differentiation factor 88 expression. Taken together, the results suggest that the inhibitory effects of cordycepin on LPS-stimulated inflammatory responses in RAW 264.7 macrophages are associated with suppression of mitogen-activating protein kinases and activation of NF-κB by inhibition of the Toll-like receptor 4 signaling pathway. Keywords: cordycepin, anti-inflammation, mitogen-activated protein kinases, NF-κB, Toll-like receptor 4